2013
DOI: 10.1016/j.jad.2013.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Posterior cerebellar vermal deficits in bipolar disorder

Abstract: Background Based on growing evidence of the crucial role of the cerebellum in emotional regulation, we sought to identify cerebellar structural deficits in a large sample of patients with bipolar disorder (BD). Methods Cerebellar gray matter density was examined in 49 BD patients (24 medication-naive and 25 medication-treated) and 50 carefully matched healthy individuals, using voxel-based morphometry with a high-resolution spatially unbiased atlas template of the human cerebellum. This recently developed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 62 publications
2
36
1
2
Order By: Relevance
“…Our study showed no differences in GM volume in the vermis areas of BD patients and healthy controls, similar to in other previous MRI studies [23,25,32]. A possible explanation for our negative results could be related to cerebellar morphology, which exhibits subtle changes that might not be identified by conventional structural neuroimaging techniques [25].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study showed no differences in GM volume in the vermis areas of BD patients and healthy controls, similar to in other previous MRI studies [23,25,32]. A possible explanation for our negative results could be related to cerebellar morphology, which exhibits subtle changes that might not be identified by conventional structural neuroimaging techniques [25].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in our study, earlier onset of the disease was associated with a greater reduction in the volume of the vermis and its subareas in males with BD. Therefore, it is plausible that chronicity, due to an earlier disease onset, may induce earlier and faster neurodegenerative processes, as reported by several [13,31,32,33,34] but not all studies [21]. It has to be noted that our findings are mainly driven by gender, being significant in male patients only.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…En el TB, las alteraciones del cerebelo incluyen reducciones de la sustancia gris (Kim et al, 2013) y blanca (Canales-Rodriguez et al, 2013), sugiriendo el posible rol de las anomal铆as del cerebelo en las alteraciones de la percepci贸n temporal en este trastorno.…”
Section: Temporalidad Y Psicosis Afectivaunclassified